ANALISIS PENERAPAN AKAD MURABAHAH DI BMT MANDIRI SEJAHTERA CABANG BABAT LAMONGAN PADA PENGEMBANGAN SEKTOR PERTANIAN DI DESA KEDUNGWARAS MODO LAMONGAN - Mochammad Afif (Al Hikmah: Jurnal Studi Keislaman, 2021)
Abstract, Baitul Maal Wat Tamwil (BMT) is a micro lembaga keuangan sharia inIndonesia. As a microfinance institution, where BMT is expected to reach the smallcommunities that are not reached by the Bank. While on the other hand, theagricultural sector is one of the sectors of society that are still accessible by bankinginstitutions that exist in Indonesia. Whereas the agricultural sector is one of the pillarsof the national economy as Indonesia is an agricultural country. From the abovebackground, there were some formulation of the problem: first, how the loan productmurabahah in BMT Mandiri Sejahtera branch Babat Lamongan second, how thefinancing murabahah in developing agriculture in the village Kedungwaras ModoLamongan by BMT Mandiri Sejahtera branch Babat Lamongan.The purpose of theabove research in general is to know more details about the financing murabaha isapplied BMT Sejahtera Mandiri Branch Babat Lamongan for agriculturaldevelopment in the village Kedungwaras Modo Lamongan. This research is a fieldresearch using qualitative descriptive approach which aims to get the data from theinformant about the analysis of the application of murabahah in the development ofagriculture in the village Kedungwaras Modo Lamongan is applied from the BMTMandiri Sejahtera Branch Babat Lamongan, then researchers mendeskriptifkan to theconclusion with using the method of observation, documentation, and interviews. Thestudy concluded that BMT Mandiri Sejahtera in the village of the DistrictKedungwaras Modo Lamongan regency is one of the BMT which is in the midst of themajority community livelihood as farmers. Therefore, BMT has a loan product that isdevoted to the farmers, namely murabaha financing the seasonal period. Financingwhere repayment is done at the end of the growing season or after harvest. Inaddition, BMT Mandiri Sejahtera also undertake joint liability financing wherefinancing is channeled to Gapoktan and managed jointly with the farmers involved inthe Gapoktan. Of the financing of these farmers can feel the progress is very good.Keywords: Application Akad Murabaha, Agriculture in the village KedungwarasModo Lamongan, BMT Sejahtera Mandiri branch Babat Lamongan